1983
DOI: 10.1039/c39830000323
|View full text |Cite
|
Sign up to set email alerts
|

A new cyclic peptide, ascidiacyclamide, isolated from ascidian

Abstract: A n e w cytotoxic cyclic peptide, ascidiacyclamide, has been isolated from ascidian and its structure has been elucidated by n.m.r. spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 0 publications
0
58
0
Order By: Relevance
“…Our interest has been in the coordination chemistry of cyclic peptides having a 24-azacrown-8-macrocyclic structure (Chart 1); these compounds have been isolated and purified from the aplousobranch ascidian Lissoclinum patella [18][19][20][21]. X-ray crystal structures of ascidiacyclamide (1) and patellamide D (2) (Chart 1) reveal two different conformations of these cyclic peptides [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Our interest has been in the coordination chemistry of cyclic peptides having a 24-azacrown-8-macrocyclic structure (Chart 1); these compounds have been isolated and purified from the aplousobranch ascidian Lissoclinum patella [18][19][20][21]. X-ray crystal structures of ascidiacyclamide (1) and patellamide D (2) (Chart 1) reveal two different conformations of these cyclic peptides [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…NMR studies have shown that the pseudo-octapeptides adopt identical conformations in solution and the solid state. 26,33,36,66,72,86 In the "saddle-shaped" conformation all nitrogen atoms point towards the inside of the macrocycle, while the "figure-ofeight" conformation is characterized by intramolecular H-bonds, N-H⋯OvC and N-H⋯O oxa (oxazoline ring), that lead to a rotation of the oxazoline rings such that the N oxa atoms face the outside of the macrocycle. 27 Several reasons for the different preferences are discussed in the literature.…”
Section: Structures and Dynamicsmentioning
confidence: 99%
“…A substantial increase in flexibility compared to the cyclic pseudo-hexa-and pseudo-heptapeptides might be expected. However, analysis of the solid state and solution structures by X-ray crystallography, 27,73,74,84,85 1 H-NMR spectroscopy, 19,33,72,85 DFT calculations 74 and molecular mechanics/ Monte Carlo/molecular dynamics-based conformational analyses 27,72 indicated that there are four conformers which we summarize here in two types of conformations: the "saddleshaped", sometimes also referred to as square, and the twisted "figure-of-eight" conformation (Fig. 4).…”
Section: Structures and Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] The Lissoclinum class of cyclic peptides, such as westiellamide (1) [4] or ascidiacyclamide (2), [5] belongs to these alkaloids and is characterized by an alternating sequence of oxazole, thiazole, oxazoline, and thiazoline moieties with hydrophobic standard amino acid residues. [6] These five-membered heterocyclic rings result from condensation of serine, threonine, and cysteine side chains with the preceding carbonyl groups in a peptide sequence.…”
Section: Introductionmentioning
confidence: 99%